Vascularized composite allotransplantation: a closer look at the banff working classification. (17th March 2016) - Schneider, Michelle; Cardones, Adela Rambi G.; Selim, M. Angelica; Cendales, Linda C.
Summary: The first Banff vascularized composite allotransplantation meeting was held in 2007 to standardize criteria for the characterization and reporting of severity and types of rejection. As a result, the 2007 Banff VCA working classification for skin allograft pathology was formalized and now serves as the standard for diagnosis of VCA rejection. Similar to other working classification systems, strengths and limitations have been identified including the adequacy of the specimen, the definition of severity between grades, the reproducibility, the adequacy of the specimens, the types of rejection, and the integration of newer technologies such as molecular and genomic approaches. Although a relatively few number of cases have been performed and followed up to date, additional phenotypes such as antibody‐mediated rejection, fibrosis, atrophy, and vascular changes are being reported and characterized based on accumulated experience in the field of VCA and parallels with other solid organs. This study aims to consider strengths and limitations of the Banff VCA working system and highlights ongoing challenges and opportunities available related to histopathology in this emerging field of transplantation.